Building better social programs : how evidence is transforming public policy - Stoesz, David (New York Oxford University Press, 2020)
"Evidence-based policymaking has, in recent decades, become a focus of program innovation in social care, engaging foundations, universities, as well as state and federal governments. Rigorous research, epitomized by Randomized Controlled Trials, have become the benchmark for demonstrating efficacy and efficiency in social programming. Building Better Social Programs situates evidence-based policymaking with respect to the welfare state, describes key organizations driving the evidence-based movement, and proposes innovations designed to extend benefits to the working-class. Interviews with leaders in the movement animate the discussion. Building Better Social Programs will be essential reading for faculty, program managers, foundation program officers, and research students"--
Includes bibliographical references and index.
Keywords: Social service -- United States; Social work administration -- United States; United States -- Social policy